Strengthening Religious Culture in Vocational Education: The Role of Taruna in Developing Skilled and Noble Character Students - Sugiyar, Sugiyar (Postgraduate Program, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2023)
This research project is concerned with the process of strengthening the religious culture of State Vocational High School 1 Geger Madiun. The objective of this research is to elucidate the position and significant role of Taruna in the formation of an exemplary generation, characterised by proficiency and a virtuous character, in both vertical and horizontal relations. Taruna represents an educational and training activity for students in vocational high schools. Vocational high schools are synonymous with the advancement of expertise and proficiency. The reinforcement of a religious culture constitutes an essential element in the formation of an individual endowed with superior qualities. An individual may be considered superior if they possess both the requisite skills and a robust spiritual and social foundation. The data collection methods employed were observation, interview and documentation. The interactive analysis model was employed to analyse the data, comprising the following steps: data collection, data condensation, data presentation, and conclusion. The findings of the study indicate that: (1) Taruna serves to enhance the physical resilience of students, equipping them with the capacity to thrive in the professional sphere; (2) Taruna cultivates the spiritual fortitude of students, fostering a sense of personal devotion and ethical conduct; and (3) The establishment of a religious culture can be achieved by integrating spiritual piety, social piety, and proficient skills, thereby establishing a model of religious culture within the context of vocational education.